Effectiveness of Anger Management in Reducing Aggressive Behavior in Patients with Schizophrenia - Maulidya, Novarida; Puspitasari, Devi (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This study evaluated the effectiveness of anger management techniques in reducing anger-related behaviors in a 33-year-old male schizophrenic patient (RM). Research was conducted at RSJD dr. Arif Zainuddin Surakarta over four weeks (February-March 2024). Initial assessment revealed hallucinations, delusions, aggression, anxiety, and sleep disturbances stemming from emotional trauma, cognitive distortions, and environmental stressors. The intervention involved recognition of anger triggers, cognitive restructuring, relaxation techniques, and behavioral coping mechanisms through 45-60 minute structured sessions. Post-intervention results showed significant improvements, including increased awareness of anger triggers, development of self-regulation techniques (notably "ambekan dowo" breathing), better recognition of anger signs, and reduced aggressive outbursts. Despite challenges including inconsistent social support and emotional instability, findings demonstrate that tailored anger management interventions can significantly improve emotional regulation in schizophrenia patients. Recommendations include multi-faceted psychological approaches and long-term family involvement through caregiver education and structured routines.